Motif hias non-sakral seni ukir Toraja - Sofyan Salam; Muhammad Saleh Husain; Tangsi Tangsi (Seminar Nasional LP2M UNM, 2019)
This study aims to explain the type of non-sacral carving motifs, the reasons behind the making of nonsacral motifs, and public opinion about the nonsakral motif on Toraja wood carving. Source of data from artifacts in the form of non-sacred decorative motifs of Toraja carving; (2) human data sources, namely engravers, community leaders, local government officials, art educators, and cultural observers; and (3) documents containing descriptions, drawings, or photographs of non-sacred motifs of Toraja carving. Data collection techniques are observation, interviews, and documentation. Data analysis uses an interactive analysis model. The results showed that: (1) Types of motifs displayed in non-sacred carving in Toraja themed, Toraja natural scenery, Aluk Todolo ritual procession, daily activities of Toraja people, summaries of various scenes, and masks. (2) Reasons for making non-sacred carvings in Toraja, namely: (a) introducing Toraja nature and culture, (b) as souvenirs for tourists visiting Toraja, (c) for developing Toraja carving, and (d) expressing condolences in particular on the theme of the funeral procession. (3) Community opinion on non-sacred carvings in Toraja, namely (a) is a reflection of the carver's dynamics in responding to community needs, (b) according to the development era, and (c) potential non-sacred carving motifs in Toraja to be developed further. The most suitable Toraja carving art is taught traditional Toraja decorative motifs to preserve and pass on Toraja local culture to the younger generation